A SUBTITLING ANALYSIS OF SWEARING WORD IN 48 HOURS MOVIE - SETIAWAN, BUDI (2010)
The purposes of this research are to describe the strategy of subtitling of swearing word in the 48 hours movie and to describe the accuracy of subtitling strategy of swearing word in 48 hours movie This research is a descriptive study by using the technique of collecting data, classifying the data and followed by drawing conclusion based on the data analysis. The data source are the 48 hours movie and the original script. The data of this research are all sentences containing swearing word in the 48 hours movie. The results of the research show that 1) the type of subtitling strategy come into four; deletion, paraphrase, transfer, and condensation. From 86 data they are deletion strategy (28 data or 32,56%), paraphrase (28 data or 32,56%), transfer (10 data or 11,63%), and condensation (11 data or 12,79%) ; 2) deletion and paraphrase common as the startegy who have many data than the other ;3) the accuracy of subtitling swearing word in 48 hours movie is on accurate level because the accurate level have 39 data or 45,35% in result. While inaccurate data have 37 data or 43,02%. The accuracy of those strategy prove that the subtitling in 48 hours movie is accurate.